Inge Citra Tingkat Aktivitas Fisik Dan Komposisi Tubuh Atlet Cabor Renang Pada Masa New Normal Di Club Aac (Abdul Aquatic Course) Semarang Tahun 2021 (Indonesian Journal for Physical Education and Sport, 2021)
This study aims to find out how the level of physical activity and calculate body composition in swimming sports during the new normal period at the AAC club (Abdul Aquatic Course) Semarang in 2021. The method used is descriptive quantitative. The research sample used total sampling or used all swimming athletes at the AAC AAC (Abdul Aquatic Course) Semarang club, totaling 16 samples. Instruments for the level of physical activity using the GPAQ questionnaire from WHO in 2012 and body composition using the BIA (Body Fat Monitoring) measuring instrument. The research data analysis technique used the calculation of physical activity from the GPAQ interpretation and body composition using the BMI criteria table throughout Asia Pacific. The results of the study show that; (1) The level of physical activity of AAC (Abdul Aquatic Course) Semarang athletes is in the low category with a percentage of 70%, the medium category with a percentage of 30%; (2) The body composition of AAC (Abdul Aquatic Course) Semarang athletes is included in the category of obesity with a percentage of 22% underweight, 13% normal and 65% obese.